Heritage Language Learning Trajectories and Multiple Influencing Factors: A Multiple-Case Study of University-Aged Korean Canadians - Song, Hyekyung (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
This study explores six university-aged 1.5 and second generation Korean Canadians’ varied heritage language (HL) learning experiences and the factors that encourage and discourage HL learning in Canada. Drawing on sociocultural perspectives (Duff, 2007, 2019; Norton, 2013), this multiple-case study reveals the core HL learning domains of home, friends at school and ethnic communities, Korean media, and university classes and various familial, sociocultural, and transnational factors. The participants’ HL learning trajectories fluctuated depending on life environments, accessibility to HL learning, and their identities and different responses to social factors. This study also underscores the importance of educational inclusivity of HLs.